1999
DOI: 10.2135/cropsci1999.0011183x003900040025x
|View full text |Cite
|
Sign up to set email alerts
|

Leafy Reduced‐Stature Maize Hybrids for Short‐Season Environments

Abstract: Development of maize (Zea mays L.) types that produce leaf area quickly and mature rapidly may increase maize yields in mid-to shortseason areas. The leafy (Lfyl) and reduced-stature (rdl) traits each contribute to this objective; however, these two traits have not previously been combined. Our objective was to determine the effect of these traits, alone or in combination, on morphology, reproductive development, and yield of maize hybrids. A field experiment including 14 hybrids [two non-leafy reduced-stature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 0 publications
4
33
2
4
Order By: Relevance
“…The observed variation in plant and ear height may be attributed to differences at the genotypic level. Dijak et al (1999) who also reported significant amount of variability among long and short stature maize populations for ear and plant height. Tassel length was highest 42 (RML-6) to lowest 14 .…”
Section: Resultsmentioning
confidence: 97%
“…The observed variation in plant and ear height may be attributed to differences at the genotypic level. Dijak et al (1999) who also reported significant amount of variability among long and short stature maize populations for ear and plant height. Tassel length was highest 42 (RML-6) to lowest 14 .…”
Section: Resultsmentioning
confidence: 97%
“…It plays a key role in the world food economy by feeding people and being raw industrial materials. Grain moisture (GM) at harvest is of primary importance for maize production and breeding since crops with low GM at harvest can reduce the economic impact of artificial drying (Dijak et al 1999;Sweeney et al 1994). On average, the GM is about 30 % at harvest in the Northern spring maize growing region, the main maize production area in China.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the larger leaf area above the ear, the vegetative period of leafy genotypes is shorter and the grain-filling period longer (Begna et al, 2001;Modarres et al, 1997). This has a positive effect both on the yield and on grain quality, as reported by a number of authors (Stewart and Dwyer, 1993;Begna et al, 2001;Modarres et al, 1997;Dijak et al, 1999). The chemical quality and digestibility of the silage is just as important as the achievement of high fresh and dry matter yields per hectare.…”
Section: Introductionmentioning
confidence: 85%